Kinerja Karyawan pada Badan Pusat Statistik Kabupaten Sukoharjo: Pengaruh Pelatihan dan Pengembangan Karir - Septiyanitha Dwi Maharani Putri; Indra Hastuti; Agus Suyatno (Jurnal Publikasi Ilmu Manajemen, 2024)
This study aims to determine the effect of training, career development and level of welfare on employee performance employees at the Central Bureau of Statistics Sukoharjo Regency. The method used in sampling is a saturated sample with a total of all respondents were 40 employees. Data collection is done by distributing questionnaires directly. The analysis technique used was SPSS 25. The results showed that: (1) Training has a positive and significant effect on employee performance at the Central Bureau of Statistics of Sukoharjo Regency with the results of the t count hypothesis of 3.216 and a significant value of 0.003 <0.05 (2) Career Development has a positive effect and significant to employee performance at the Central Bureau of Statistics of Sukoharjo Regency with the results obtained t count of 2.355 and a significant value of 0.024 <0.05, (4) Training and Career Development on employee performance employees at the Central Bureau of Statistics of Sukoharjo Regency with the results obtained f count of 439.010 and a significant value of 0.000 < 0,05.